Effects of heat waves on urban warming across different urban morphologies and climate zones. (1st February 2022) - Mohammad Harmay, Nurul Syahira; Choi, Minha
Abstract: Heat wave (HW) periods, which are characterized by unusual high temperatures and heat stress, are known as one of the global issues that negatively affect the land and atmosphere, especially in urban areas. Higher urbanization rates in cities may result in high temperature warming, which is known as the Urban Heat Island (UHI). Recently, researchers have revealed pronounced effects based on HW and UHI interactions; however, studies that linked their effects with surface energy fluxes in different urban landscape and climate are still inadequate. This study utilized the Community Land Model (CLM) to assess the effect of HW towards UHI, while considering energy fluxes variations in Seoul, Tokyo, Kuala Lumpur, and Melbourne, with different climate influences and urban morphologies. Generally, Seoul and Tokyo showed intense HW magnitude from 2000 to 2018 based on the HW indices. The surface energy flux components demonstrated a distinct pattern especially from 11:00 to 17:00, with the exception of sensible heat in Melbourne. Further energy-flux partitioning revealed that changes in the heat storage ratio were most significant in Seoul, with 1.39 partitioning due to its larger impervious area. A smaller height-to-width (H/W) canyon ratio of open mid-rise building has enhanced urban warming in Melbourne, whereas smaller impervious and larger pervious road fraction could mitigate urban warming effects in Kuala Lumpur. Seoul showed the highest changes in daytime UHI under HW at 2.01 °C, due to the low convection efficiency in compact high-rise building, while nighttime UHI was highly influenced by heat storage and anthropogenic heat release. Highlights: Seoul and Tokyo have more intense heat waves (HWs) during 2000–2018. Latent heat, heat storage, and net radiation changed consistently from 11:00 to 17:00 during HW events. City that has compact building type contributed to the highest heat storage ratio. Smaller height-to-width (H/W) canyon ratio enhanced urban warming under HWs. Urban heat island was enhanced under HW occurrences.